2014
DOI: 10.1038/gt.2014.35
|View full text |Cite
|
Sign up to set email alerts
|

rAAV9 combined with renal vein injection is optimal for kidney-targeted gene delivery: conclusion of a comparative study

Abstract: Effective gene therapy strategies for the treatment of kidney disorders remain elusive. We report an optimized kidney-targeted gene delivery strategy using recombinant Adeno-Associated Viruses (rAAV) administered via retrograde renal vein injection in mice. Renal vein injection of rAAV consistently resulted in superior kidney transduction compared to tail vein injection using as little as half the tail vein dose. We compared rAAV 5, 6, 8 and 9, containing either GFP or luciferase reporter genes driven by the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 56 publications
(53 reference statements)
1
63
0
1
Order By: Relevance
“…43,46,48 Different AAV serotypes have different tissue transduction efficiencies and more recent data suggest that rAAV2/9 may be the preferred choice for future renal gene delivery. 4952 However, rAAV2/9-mediated transgene expression in the kidney is still significantly lower than that in the liver. Using a retrograde renal vein injection method, Rocca et al .…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…43,46,48 Different AAV serotypes have different tissue transduction efficiencies and more recent data suggest that rAAV2/9 may be the preferred choice for future renal gene delivery. 4952 However, rAAV2/9-mediated transgene expression in the kidney is still significantly lower than that in the liver. Using a retrograde renal vein injection method, Rocca et al .…”
Section: Treatmentmentioning
confidence: 99%
“…Using a retrograde renal vein injection method, Rocca et al . 52 showed that rAAV2/9-mediated kidney transduction could be markedly improved. Identification of viral serotypes that effectively transduce all affected tissue types remains to be further explored.…”
Section: Treatmentmentioning
confidence: 99%
“…Future electron microscopy studies may elucidate this mechanism further. The retrograde nature of the injection has precedence in that the hydrodynamic tail vein injection method reverses the flow of the hepatic vein 20 and other successful methods of kidney transfection have injected via the renal vein 1214,21 . Kidney damage is likely required for optimal transfection efficiencies so we hypothesize that transfection occurs via damage to the cell membrane caused by the fast, high-volume injection.…”
Section: Discussionmentioning
confidence: 99%
“…Also, its use has been reported to be safe and effective in various clinical trials [97][98][99][100][101]106,109]. With respect to gene delivery, different approaches can be used to target the kidney to achieve expression of the transgene in proximal and distal tubules, glomeruli, and the peritubular interstitium [106,111,112]. With respect to gene delivery, different approaches can be used to target the kidney to achieve expression of the transgene in proximal and distal tubules, glomeruli, and the peritubular interstitium [106,111,112].…”
Section: Gene Therapymentioning
confidence: 99%
“…There are various variants (>10) of AAV available; these are referred to as "serotypes," and each has different tissue-specific induction capacities [110]. For example, it was recently shown that injection of recombinant AAV serotype 9 in the murine renal vein is effective for renal transgene expression [112], and a retrograde approach successfully induced transgene expression in the renal tubular epithelium in cortex and medulla using recombinant AAV serotype 2 [106,112]. For example, it was recently shown that injection of recombinant AAV serotype 9 in the murine renal vein is effective for renal transgene expression [112], and a retrograde approach successfully induced transgene expression in the renal tubular epithelium in cortex and medulla using recombinant AAV serotype 2 [106,112].…”
Section: Gene Therapymentioning
confidence: 99%